Deciphering the role of the two metal–binding sites of DapE enzyme via metal substitution. (April 2023) - Paul, Atanuka; Mishra, Sabyashachi
Abstract: DapE is a microbial metalloenzyme that hosts two Zn ions in its active site, although it shows catalytic activity with varying efficiency when the Zn ions in one or both of its metal–binding sites (MBS) are replaced by other transition-metal ions. The metal-ion promiscuity of DapE is believed to be a microbial strategy to overcome the homeostatic regulation of Zn ions by the mammalian host. Here, a hybrid QM/MM study is performed on a series of mixed-metal DapEs, where the Zn ion in the first MBS (MBS–1) is substituted by Mn, Co, Ni, and Cu ions, while the MBS–2 is occupied by Zn(II). The substrate binding affinity and the mechanism of catalytic action are estimated by optimizing the intermediates and the transition states with hybrid QM/MM method. Comparison of the binding affinity of the MBS–1 and MBS–2 substituted DapEs reveals that the MBS–1 substitution does not affect the substrate binding affinity in the mixed-metal DapEs, while a strong metal specificity was observed in MBS–2 substituted DapEs. On the contrary, the activation energy barriers show a high metal specificity at MBS–1 compared to MBS–2. Taken together, the QM/MM studies indicate that MBS–2 leads the substrate binding process, while MBS–1 steers the catalytic activity of the DapE enzyme. Graphical Abstract: ga1 Highlights: Microbial enzyme DapE is crucial for bacterial growth and survival, and is a potential antibiotic target. QM/MM study of catalysis by mixed-metal DapE, with Zn(II) in metal-binding site (MBS) 1 replaced by Mn, Co, Ni, and Cu ions. MBS–2 shows strong metal specificity for substrate binding and MBS–1 shows high metal specificity for chemical catalysis. The Co-substituted mixed-metal Co-Zn DapE outperforms the catalytic activity of the wild-type DapE.